IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN PATENT SYSTEMS: A SYSTEMATIC LITERATURE REVIEW ON EFFECTIVENESS AND LEGAL IMPLICATIONS - Andi Istiana Inayah Dwi Putri; Anugrah Ade Putra (PT. Jurnal Center Indonesia Publisher, 2025)
The integration of artificial intelligence (AI) in patent systems has emerged as a complex area in intellectual property law. This systematic literature review follows PRISMA 2020 guidelines to analyze AI implementation in patent systems, particularly within the Indonesian context. The study examines 11 key studies published between 2015-2025 through systematic searches across multiple academic databases. Results demonstrate that AI implementation has achieved significant improvements in operational efficiency, particularly in automated patent classification, prior art searching, and examination support systems. Approximately 190,000 AI patents were granted globally between 2000-2022, reflecting increasing technological importance. In Indonesia, AI implementation must align with Law No. 13 of 2016 on Patents as amended by Law No. 65 of 2024. The landmark Thaler v. Vidal case confirms AI cannot be an